Development of a Hg-free UV light source and its performance in photolytic and photocatalytic applications. Issue 2 (23rd November 2018) - Horikoshi, Satoshi; Yamamoto, Daisuke; Hagiwara, Kenta; Tsuchida, Akihiro; Matsumoto, Isamu; Nishiura, Yoshinari; Kiyoshima, Yousuke; Serpone, Nick
Abstract : Constraints on light sources that use mercury (arc lamps) are evolving with the establishment of the Minamata Convention, which has led to the proliferation of LEDs. Abstract : Constraints on light sources that use mercury (arc lamps) are evolving with the establishment of the Minamata Convention, which has led to the proliferation of LEDs. However, no LED light source emits intense ultraviolet radiation at wavelengths below 300 nm for photolytic applications. Thus, it is necessary to develop suitable UV light sources for the decontamination of wastewater and water sterilization processing. Herein, we explore various substitute gases ( e.g., N2, Ar, He and SF6 ) to replace mercury, which is commonly employed in arc lamps, using an EL (electroluminescence) quartz assembly platform similar to microwave-discharge electrodeless lamps. Although nitrogen is an inexpensive and safe gas, it cannot generate significant UV radiation in the UVC region of 200–300 nm. This problem in the Hg-free light source was resolved by mixing a very small quantity of sulfur hexafluoride (SF6 ) as an additive filler gas in a nitrogen-, argon- or helium-filled assembly. The low-pressure mercury lamp consisting of Hg/Ar filler gases is ca . 25% more efficient than the novel N2 /SF6 lamp toward the photolytic decomposition of Rhodamine-B (RhB) dye-contaminated wastewater (1.66 × 10 −4 mM min −1 versus 1.22 × 10 −4 mM min −1 ). Nonetheless, the latter has proven far more efficient than an LED source emitting 365 nm radiation (0.057 × 10 −4 mM min −1 ). The addition of TiO2 to RhB-contaminated wastewater demonstrated that this Hg-free N2 /SF6 light source is as efficient as the corresponding Hg/Ar electroluminescent lamp toward the photocatalytic decomposition of the RhB dye pollutant.